Anticancer Activity Evaluation of New Thieno[2,3-d]pyrimidin-4(3H)-ones and Thieno[3,2-d]pyrimidin-4(3H)-one Derivatives - Olga Shyyka; Nazariy Pokhodylo; Nataliya Finiuk; Vasyl Matiychuk; Rostyslav Stoika; Mykola Obushak (MDPI AG, 2018)
Anticancer screening of several novel thienopyrimidines has been performed. The thienopyrimidine derivatives were synthesized from available starting materials according to the convenient synthetic procedures using a one-pot solvent-free reaction which gave a wide access to thienopyrimidine-derivative production. The synthesized compounds were preselected via molecular docking to be tested for their anticancer activity in NCI 60 cell lines. It was observed that some compounds showed remarkable anticancer activity. It was found that the most active compound among thieno[2,3-d]pyrimidine-4(3H)-ones is 2-(benzylamino)-5,6-dimethylthieno[2,3-d]pyrimidin-4(3H)-one, which possesses cytotoxic activity on almost all cancer cell lines with mean growth 51.01%, where the most sensitive was the melanoma cell line MDA-MB-435 with GP (Growth Percent) = −31.02%. The patterns of structure–activity that are important for further optimization of the structure and the creation of more selective and active anticancer agents were proposed.